(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Today, it aims to improve the quality of learning and make language acquisition more effective. Vocabulary is central to speaking skills and overall language use. This article discusses why teaching vocabulary is the most important part of learning in foreign language.